PENGEMBANGAN KARTU FLASH CARD MATERI PENGURANGAN MELALUI MODEL KAMP MENINGKATKAN SELF EFFICACY: DEVELOPMENT OF SUBTRACTION FLASH CARDS THROUGH CAMP MODEL TO INCREASE SELF EFFICACY - Pratama, Adha; Amalia, Shofi Nur; Fatih, Muhammad (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2025)
The objectives of this study are to: (1) outline the steps involved in creating instructional materials based on flashcards that teach subtraction of numbers 1–10 using the Kemp Model; (2) evaluate the media's viability and validity using expert assessments; and (3) investigate how the media affects Grade I students at SDN 2 Kalipucung, Blitar Regency, in terms of their increased self-efficacy. Using a research and development (R&D) methodology, the study concentrated on creating and assessing cutting-edge educational materials for use in primary school. Pretest–posttest measures of self-efficacy, student response questionnaires, and expert validation sheets were among the tools used to collect data. According to validation results, the media was very feasible in the opinion of media and subject matter experts. Additionally, after using the media, students' self-efficacy significantly increased, as evidenced by effectiveness testing, which showed average scores moving from the